TINDAK TUTUR EKSPRESIF MENGELUH DALAM ANIME ANI NI TSUKERU KUSURI WA NAI SEASON 4 - Dena Fath Malik (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Modal Intelektual, Universitas Widyatama, 2023)
Speech acts refer to utterances expressed by speakers while performing an action and purpose with a specific meaning to elicit an expected response from the interlocutor. They can be categorized into various types according to the speaker's intention. Speech acts are divided into three types: locutionary, illocutionary, and perlocutionary. Within illocutionary acts, there are five types: assertive, directive, expressive, commissive, and declarative. Expressive speech acts can also be found in anime, along with various complaining strategies and other functions. The purpose of this research is to explore the functions of commissive speech acts and the complaining strategies used in a Japanese animated series titled